Study of seed morphology and influence of ageing and storage conditions on germination and seedling vigour of non-Basmati aromatic rice. (September 2021) - Ghosh, Mrityunjay; Gorain, Jaladhar; Pal, Ashis Kumar; Saha, Bhaswati; Chakraborti, Prabir; Avinash, B.; Pyngrope, Divya M.; Banerjee, Sibajee; Sarkar, Shrabana
Abstract: The seed quality of diverse aromatic rice landraces is of great importance in tropical and sub-tropical humid environment. The changes in seed behaviour under different storage methods and durations need to be studied to conserve the seeds in better way for sowing viable and healthy seeds toward greater rice production with premium quality. Three experiments were conducted (1) to find out distinguishable seed morphological traits and (2) to understand the effects of storage duration, container and environment on germination and seedling vigour of non-Basmati aromatic rice during 6-month period (December to June) before next growing season. Among 16 aromatic rice cultivars, genetic variations in seed length (4.8–7.5 mm), seed width (2.1–3.2 mm), test weight (10.0–15.6 g), lemma and palea colour (golden-yellow, straw-yellow, black, brownish-red, purple spot at tip on straw background) were noted. Germination rate was steadily increased up to 4 months of post-harvest storage (93.0%, CV 4.9%) and attained a plateau for next 2 months. Four landraces viz . Gandheswari, Kalonunia, Kaminibhog and Radhunipagal remained dormant up to 2 months; while Mohanbhog, Gandhamalati, Gopalbhog and Badshabhog had better germinability throughout normal storage period. Among four containers, jute-made gunny bag and earthen pot were found suitable for higher germination rate (82.7–85.0%) as well as to produce better seedlings of Radhunipagal rice stored for 6 months compared to non-biodegradable material made containers (galvanized iron bin and polypropylene bag). Besides, the use of neem leaf could favour germination speed (39.5 vs 36.1%) and seedling vigour of Radhunipagal rice than no neem leaf treatment. Storage at low temperature (8±2 °C) for 6 months appeared better for greater seedling length (20.8 vs 19.3 cm) and vigour index (1897 vs 1733) of Lal Badshabhog rice compared to ambient condition (28±4 °C). Highlights: Genetic variation in seed morphology (size, colour, awnness and test weight) among non-Basmati aromatic rice was recorded. Poor germination speed after harvest (1–2 months) and reached minimum standard. (>80%) after 4 months. Effectiveness of storage containers: Earthen pot > Jute-made bag > Galvanized iron bin > Polypropylene bag. Neem leaf ( Azadirechta indica ) in storage favoured germination speed and vigour index.